Saving transatlantic cooperation and the Iran nuclear deal : a view from Europe and the United States - Brustlein, Corentin; Dobbins, James; Kaye, Dalia Dassa; Meier, Oliver; Overhaus, Marco; Quilliam, Neil; Ries, Charles P.; Schmid, Dorothée; Vakil, Sanam; Zamirirad, Azadeh (2018)
Zusammenfassung: Transatlantic differences over the future of the Iran nuclear deal - or the Joint Com-prehensive Plan of Action (JCPOA) of July 2015 - are damaging a nuclear accord that all parties, except the United States, see as delivering on its purpose. They also increase the risk of Washington and European capitals working at cross-purposes vis-à-vis Iran and broader regional policies. To avoid such a scenario, the E3 (France, Germany, United Kingdom)/European Union (EU) and the United States need to set up new channels of communication to avoid a transatlantic rift, to attempt - if at all possible - to preserve the Iran deal, and to secure its benefits for regional and global security